Penerapan Sistem Pengembangan Produk dengan Metode Kanban Untuk Meningkatkan Industri Kain Sasirangan - Yusri Yusri; Muhammad Rizali; Munawar Munawar; Hartati Hartati; Risma Liana Putri; M. Rifky Rais (Pusat Riset dan Inovasi Nasional, 2025)
Sasirangan cloth is a traditional cloth typical of South Kalimantan which is full of cultural values ​​and the philosophy of the Banjar people. Despite its promising economic potential, many craftsmen still experience business sluggishness due to the lack of a structured development strategy. This program aims to implement the Kanban method to support the development of the sasirangan cloth industry, including the creation of derivative products as an alternative to regional souvenirs. Implemented in Banjarmasin and Banjar Regency in January-February 2025, activities include the application and socialization of the Kanban method to craftsmen of the Paguyuban Barakat Cangkal. The results are prototypes of derivative products such as miniatures of the Zero Kilometer Monument and the Observation Tower. Visualizing the production process through the Kanban method helps partners understand and be interested in implementing this system to increase the efficiency of their businesses.